1997
DOI: 10.1126/science.277.5328.965
|View full text |Cite
|
Sign up to set email alerts
|

AIB1, a Steroid Receptor Coactivator Amplified in Breast and Ovarian Cancer

Abstract: Members of the recently recognized SRC-1 family of transcriptional coactivators interact with steroid hormone receptors to enhance ligand-dependent transcription. AIB1, a member of the SRC-1 family, was cloned during a search on the long arm of chromosome 20 for genes whose expression and copy number were elevated in human breast cancers. AIB1 amplification and overexpression were observed in four of five estrogen receptor-positive breast and ovarian cancer cell lines. Subsequent evaluation of 105 unselected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
1,050
6
9

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,496 publications
(1,101 citation statements)
references
References 15 publications
36
1,050
6
9
Order By: Relevance
“…NCOA3 has been detected as being amplified in breast cancer (synonym AIB1). 26 It has also been described to be amplified in endometrial, stomach, prostate, pancreatic, and hepatocellular carcinomas. [27][28][29] NCOA3 is as transcription coactivator involved in cell proliferation, migration, differentiation, and growth.…”
Section: Discussionmentioning
confidence: 99%
“…NCOA3 has been detected as being amplified in breast cancer (synonym AIB1). 26 It has also been described to be amplified in endometrial, stomach, prostate, pancreatic, and hepatocellular carcinomas. [27][28][29] NCOA3 is as transcription coactivator involved in cell proliferation, migration, differentiation, and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover both SRC-1 and TIF2, although widely expressed, have previously been identi®ed as competable, limiting factors particularly in the context of the squelching of progesterone receptor transactivation in the presence of ectopic ER expression (Onate et al, 1995;Voegel et al, 1996). Signi®cantly, both proteins are expressed at very modest levels in most breast tumour derived cell lines (Anzick et al, 1997;Berns et al, 1998) and levels of SRC-1 are also particularly low in patients who fail to respond to tamoxifen therapy (Berns et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The SRC-1 expression clones were in pSG5 and all based on the SRC-1e isoform and expressed at comparable levels (Kalkhoven et al, 1998;Bevan et al, 1999). AIB1 and TIF2 expression constructs have been described elsewhere (Anzick et al, 1997;Voegel et al, 1996). Cell monolayers were transiently transfected and subsequently hormonally manipulated as described previously (Bates and Hurst, 1997).…”
Section: Transient Transfection Assaysmentioning
confidence: 99%
“…However, overexpression of AIB1, GRIP1, PELP1, MUC1, breast carcinoma amplified sequence 3 (BCAS3), Ciz1, SRA has been shown to induce breast carcinogenesis [172]. AIB1 and BCAS3 are both ERα coactivators known to be amplified, overexpressed, and associated with tamoxifen resistance in breast cancers [173,174]. A recent clinical study using 560 human breast tumor tissues found the AIB1 expression along with expression of genes involved in cell migration and invasion such as polyomavirus enhancer activator 3 and matrix metalloproteinases 2 and 9 suggesting a positive correlation of AIB1 expression with tumor metastasis [95].…”
Section: Estrogen Receptor Coregulators In Breast Cancer Coactivatorsmentioning
confidence: 99%